Información General: Instituto de Inmunología Clínica (IDIC) - Universidad de Los Andes (SABER ULA, 2008)
The Institute of Immunology of the Faculty of Medicine of the University of the Andes is an agency oriented by principles of excellence, the innovation and technical development and scientific for the service of institutional advancement and for the collective welfare of the nation in general and in particular. Its academic work is focused in the completion of the task of education, investigation and service in the maintenance of excellent relations with the institutions of support for the activities and utilization of the results produced in the Institute. It's headquarters is the Faculty of Medicine of the University of the Andes in the University Hospital of the Andes in the city of Mérida, realizing some of it's activities in other hospitals and centers of assistances located in cities of the region which, the Faculty maintains academic relations.
Keywords: Inmunología celular; Inmunoparasitología; Inmunopatogenia de las hepatitis virales; Inmunopatogenia de las infecciones inducidas por retrovirus (HTLV-I y II); Inmunodeficiencias primarias y secundarias; Medicina y Salud; Biología; Cellular immunology; Escuela de Medicina; Facultad de Medicina; Núcleo Mérida; Facultad de Medicina; Núcleo Mérida; Instituto de Inmunología Clínica (IDIC); Immunoparasitology; Immunopathogens of viral hepititis; Immunopathogens of the infections induced by retrovirus (HTLV-I y II); Immunodeficiency's primary and secondary; Instituto de Investigación; Medicine and Health; Biology; Unidades de investigación